performance of accreditation surveyors in Tehran hospitals: Strengths and weaknesses - ebrahim jaafaripouyan; alimohammad mosadeghrad; abbas salarvand (Tehran University of Medical Sciences, 2018)
Background: Accreditation is one of the health sector evaluation methods that used to promote healthcare quality. The study aimed to identifiy the strength and weakness of accreditation surveyors and the impact of their performances. Materials and Methods: This study is a qualitative research which conducted between hospital accreditation stakeholders in 2016- 2017. Data were gathered using semi-structured interviews and analyzed by a thematic analysis method. Results: The findings of in strengthen were categorized in 7 themes. The main strengthen was acceptance of accreditation by surveyors, educational approach, reputation, personal effort to develop knowledge and skills, and existence of senior surveyors. Our results for weakness were classified in 8 themes. The main weaknesses were lack of sufficient knowledge, experience, skills and weakness in personal characteristics. Based on the findings, the accreditation surveyors' performance was evaluated as under-moderate in past two periods of hospital accreditation. The interviewees announced that weakness of surveyors' performances was one of the main effective factors of low stability of accreditation results. Conclusion: Recruitment of surveyors based on main competence, education and empowerment of surveyors, and assessing the surveyors can lead to more validity of accreditation results and finally lead to increasing the commitment of hospitals to quality.